The role of Dickkopf-3 overexpression in esophageal adenocarcinoma - Wang, Zhuwen; Lin, Lin; Thomas, Dafydd G.; Nadal, Ernest; Chang, Andrew C.; Beer, David G.; Lin, Jules (The Journal of thoracic and cardiovascular surgery, 2015)
Ninety percent of patients with esophageal adenocarcinoma ultimately die of their disease, highlighting the need for novel therapeutic targets. The goal of this study was to define the functional significance of overexpression of Dickkopf-3 (DKK3) in esophageal adenocarcinoma. DKK3 expression was analyzed by real-time polymerase chain reaction in 95 chemonaive and 21 chemoresistant esophageal adenocarcinomas. The esophageal adenocarcinoma cell line OE33 was stably transfected with DKK3 (OE33/DKK3) and evaluated using WST-1 (Roche, Basel, Switzerland), Matrigel (BD Biosciences, San Jose, Calif), endothelial tube formation, and chemosensitivity assays. Tumorigenesis was evaluated by injecting 1 × 106 OE33/DKK3 and vector cells in NOD/SCIDγ mice. DKK3 was overexpressed (>2-fold) in 75.8% (72/95) of esophageal adenocarcinomas. DKK3 protein was present at moderate to high levels in 46.8% (29/62) of esophageal adenocarcinomas on tissue microarray. Stable transfection of DKK3 significantly increased proliferation (P < .05) and Matrigel invasion (P < .001). Levels of SMAD4, a key mediator of the transforming growth factor-ß pathway, increased after activin treatment of OE33/DKK3, and siSMAD4 significantly decreased Matrigel invasion, suggesting that DKK3 acts through the transforming growth factor-β pathway. OE33/DKK3 cells increased endothelial tube formation and were significantly more resistant to 5-fluorouracil and cisplatin, and DKK3 expression was significantly higher in chemoresistant esophageal adenocarcinomas (P < .005). In NOD/SCIDγ mice, OE33/DKK3 cells resulted in tumors at all sites (8/8), whereas vector cells grew in only 1 of 8 sites. Nodal metastases were also significantly increased in patients with esophageal adenocarcinomas highly overexpressing DKK3, 28 of 32 (88%) versus 42 of 63 (68%) (P < .05). These findings suggest that DKK3 may be important in mediating invasion in esophageal adenocarcinoma and could be a novel target in the treatment and prevention of metastatic disease.